PENGARUH TERPAAN INFORMASI MELALUI SALURAN MEDIA KONVENSIONAL, MEDIA DIGITAL, DAN KOMUNITAS TERHADAP PARTISIPASI PROGRAM PEMERIKSAAN KESEHATAN GRATIS HARI ULANG TAHUN DI KOTA SEMARANG - Bintang Ayutria Amanda Wahyu; Yanuar Luqman (Interaksi Online, 2026)
The government launched a program called the Free Birthday Health Checkup to promote health development for the entire community. Efforts to disseminate information have been made, but public participation in the program remains low. Using a quantitative approach with an explanatory research approach, this study shows that exposure to information through conventional media, digital media, and community groups does not significantly influence public participation. Most respondents participated in the program at the invitation of health care workers at community health centers.